Seleksi Penerimaan Karyawan Baru Menggunakan Metode Topsis - Yessica Siagian (Jurnal Mantik Penusa, 2018)
Employee acceptance is the most important thing for a company to obtain a new competent employee. Employees are the main assets of companies that become planners and active actors of organizational activity. In some companies, the process of receiving new employees is still not done professionally. So often we find new employees coming into a company only survive in a short time only. The main reason is the recruitment error. To solve these problems required analytical techniques that can assist corporate management in making decisions to determine new employees at PT. Indah Jaya. The method used in this research is TOPSIS (Techinique for Order Preference by Similarity to Ideal Solution) method which is one of the methods in Decision Support System (SPK). Through the application of this method, researchers can compare each prospective employee based on the criteria that determine the prospective employee is considered qualified. Such as education criteria, work experience, skills / abilities, age, character and other criteria.